Development of Subunit Vaccine against Poultry Coccidiosis - Ramalingam, Vijayashanthi; Muthusamy, Raman; Bohra, Kasthuri; Nithyanantham, Madan; Palavesam, Azhahianambi; Gopal , Dhinakarraj (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Coccidiosis has a major impact on the economy of the poultry industry worldwide, caused by the protozoan parasite of the genus Eimeria inhabiting the intestinal tract and caecum. The current method of prophylactic use of anti-coccidial drugs led to the emergence of drug resistant isolates with the presence of drug residues in meat and egg. Of the alternate control strategies available, use of recombinant protein-based vaccines was reported to achieve 30 to 90% reduction in parasite replication with a reduction in intestinal lesion score and improved feed conversion ratio along with bodyweight gain. In the present study, an immunization trial was conducted on 75 chickens using the bivalent recombinant candidates comprising of gametocyte antigen (Gam82) from Eimeria maxima and microneme protein 1 (EtMIC1) from Eimeria tenella had been found to offer higher protection against the experimental challenge using field isolates of mixed Eimeria oocysts (as Group III) for upto 69.23% than those two recombinant protein namely Gam82 (Group I- 34.49%) and EtMIC1 (Group II- 46.15%) given separately, for up to 6 weeks of post-immunization.